O Emílio na contramão da educação instituída - Araújo, Sarah da Silva (2019)
The dissertation “Emilio in the backward way of instituted Education” is a result of the readings, discussions and reflections with the Line of Research of Education, School and Technologies of the interdisciplinary Post Graduate Program in Education, Language and Technologies of the State University of Goiás. The research aims to present the imaginary student of Rousseau, as well as the forward way and the backward way which the title refers being the first one that refers to the established society and the latter the one in which Rousseau educates his Emilio. For this, the first chapter is dedicated to presenting the main theories of the philosopher, as the conception of state of nature, social state, perfectibility and the context in which Rousseau writes. In the second chapter is presented the forward way and backward way are shown and why Emilio is in the way backward, since his education goes against the one we have. This work refers not only to Rousseau’s society of XVIII century and not only to the present day, but in a society in an universal sense, and in this sence, during the development of the work we realize that Emilio is in the backward way because he is educated accorting to the state of nature, but to inquire the present state in which we live. Rousseau educated Emilio with freedom and autonomy to performe well any task he proposes to do, distancing him from the venal man of our society. This work was carried out through a bibliographical research, where Rousseau’s main works were read as well as their commentators, in addition to authors who contributed to a better understanding of the social scene of the time. We conclude presenting the ideas of the Greeks in the classical antiquity, where the secret for a good education was the restraint of feelings and attitudes, that is, the middle ground in all action, wich is present in Rousseau’s student.